Impact of Inclusive Culture and Work Environment on Employee Performance with Job Satisfaction as a Mediator - Nurna Pratiwi; Dwi Irma Agustiani; Rifqi Syarif Nasrulloh (Research Synergy Foundation, 2025)
This study examines and analyzes the influence of inclusive culture and work environment on employee performance, with job satisfaction serving as a mediating variable. The population consisted of 190 female employees in the Special Region of Yogyakarta, selected through purposive sampling. Data were collected using a four-point Likert scale and analyzed quantitatively using SEM PLS 3. The results indicate that inclusive culture has a positive effect on both job satisfaction and performance, whereas the work environment has a negative effect on job satisfaction. Job satisfaction positively influenced performance and mediated the relationship between inclusive culture and performance. This study highlights the importance of fostering a strong inclusive culture within organizations to enhance employee performance. Additionally, companies should prioritize employee skill development through training programs to improve overall job satisfaction and performance. Therefore, this study suggests that organizations should focus on creating an inclusive and supportive work environment to achieve optimal performance outcomes.